Growth of Crambe under Different Soil Bulk Densities and Water Restriction - Oliveira, C. E.S. [UNESP]; Zoz, T.; Castagnara, D. D.; Zoz, A. [UNESP]; Mortinho, E. S. [UNESP]; Fernandes, G. C. [UNESP]; Sobrinho, R. Lustosa; Faria, G. A. [UNESP] (Pleiades Publishing, 2023)
Abstract: Soil compaction and moisture conditions are crucial for the adequate performance of crops, considering their influence on the soil exploration capacity of the root system. The present study aimed to evaluate the growth and yield of crambe plants in an Oxisol with different bulk densities under two water regimes. Two experiments were conducted: the first was formed by five soil bulk densities (1.0, 1.2, 1.4, 1.6, and 1.8 Mg/m3), and the second by the same soil bulk densities under two water regimes (with and without water restriction). Plant height, stem diameter, number of grains per plant, number of branches per plant, the mass of grains per plant, shoot dry mass, and harvest index were affected by the increase in the soil bulk density. The water restriction on all soil densities affected the growth and production of crambe plants. Crambe plants are favored at densities of up to 1.4 Mg/m3 without water restriction. Adequate water supply favors the development of roots in the compacted soil layer. The increase in soil density, up to 1.8 Mg/m3, negatively affects the photosynthetic system, stomatal conductance, transpiration, and leaf internal CO2 and positively affects the efficiency of water use, enhanced by the occurrence of water restriction.
Keywords: abiotic stress; Crambe abyssinica; root system; soil compaction